Julius Caesar and the Art of Rhetoric - Naphtali Rivkin (International Society of Philosophy and Cosmology, 2014)
Approaching politics through literary analysis, Julius Caesar and the Art of Rhetoric aims to answer the question, "what makes a successful politician?" Through a systematic line-by-line scru-tiny of Shakespeare's quintessential political play, Julius Caesar, Rivkin isolates "the art of rheto-ric" as the single historic constant indispensible in the ever-changing equation of political success Beyond the play, Julius Caesar, Rivkin explores rhetoricians and political philosophers like Ar-istotle, Quintilian, and Ramus who may have contributed to Shakespeare's Early Modern world-view. But Shakespeare seems to transcend his influences, and demonstrates his near prescience in a political story that is as historical as it is ahead of its time. Shakespeare touches on the timeless essence of politics, which, if understood, could inform successful political leaders and systems of tomorrow.